Use of Data Envelopment Analysis (DEA) to assess management alternatives in the presence of multiple objectives. (February 2023) - Pascoe, Sean; Cannard, Toni; Dowling, Natalie A.; Dichmont, Catherine M.; Asche, Frank; Little, L. Richard
Abstract: Marine ecosystem-based management often aims to satisfy a wide range of economic, social and environmental objectives. These are often measured in non-commensurable units, making identification of a preferred option difficult when outcomes and measures vary considerably. In this paper, we examine the potential for data envelopment analysis (DEA) as an alternative approach to traditional multi-criteria decision analysis (MCDA). We derive multi-output composite indicator scores for three case study examples. The management alternatives are assessed both with and without exogenously determined objective preference weights. The frontier-based analysis does not require weights to be assigned to each objective, instead generating flexible "benefit of the doubt" weights that allow for different objectives to be influencing each management option. Applying stakeholder objective importance weights allows the assessment of the objective alignment of the different stakeholder groups, providing additional information on management option performance. The DEA results were found to be consistent with those from an earlier study that used a more traditional MCDA approach. DEA has the additional advantage of not requiring measures to be commensurable and can also directly incorporate undesirable outcomes into the analysis. Highlights: DEA can rank management options against social, economic and environmental outcomes. DEA has advantages in dealing with non-commensurate data and undesirable outcomes. DEA can include model generated and expert opinion-based outcome measures. DEA is applied to three case studies to test its applicability to support management.